Admiral's Light - Rideout, Henry Milner, 1877-1927; Justice, Martin, 1869-1961; Woodbury, Charles H. (Charles Herbert), 1864-1940 (Salt Lake City, UT : Project Gutenberg, 2018)
"Admiral's Light" by Henry Milner Rideout is a novel written in the early 20th century. The story unfolds around Miles Bissant, a young boy tasked with maintaining the lighthouse, as he navigates life in a small coastal community filled with unique characters and a sense of adventure. The narrative explores themes of family legacy, personal identity, and the transition from childhood innocence to the burdens of growing up. The opening of the novel introduces Miles, who performs his nightly duties at the lighthouse, revealing a blend of boyish wonder and the weight of responsibility. We meet characters such as Miles's grandfather, who embodies a stern authority, and the enigmatic sailor Captain Florio, who brings a spark of excitement into Miles's life. A chance encounter with a traveling magician and his daughter Anna Hilliard sets the stage for Miles's youthful curiosity and future adventures. The interactions between Miles and these characters hint at the complexities of relationships, challenges of familial expectations, and the youthful desire for independence that will shape Miles's journey throughout the story. (This is an automatically generated summary.)
Release date is 2018-07-25
E-text prepared by Sonya Schermann, David E. Brown, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: First loves -- Fiction; New England -- Fiction; Foundlings -- Fiction; Lighthouse keepers -- Fiction